2016
DOI: 10.3390/ma9030155
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited Bacterial Adhesion and Biofilm Formation on Quaternized Chitosan-Loaded Titania Nanotubes with Various Diameters

Abstract: Titania nanotube-based local drug delivery is an attractive strategy for combating implant-associated infection. In our previous study, we demonstrated that the gentamicin-loaded nanotubes could dramatically inhibit bacterial adhesion and biofilm formation on implant surfaces. Considering the overuse of antibiotics may lead to the evolution of antibiotic-resistant bacteria, we synthesized a new quaternized chitosan derivative (hydroxypropyltrimethyl ammonium chloride chitosan, HACC) with a 27% degree of substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Thus, testing the antimicrobial properties of new compounds not only against exponentially growing bacterial cells but also against biofilms is mandatory. Ability of quaternized Ch-derivatives to interfere with biofilm formation is a promising but still relatively poorly investigated subject [37,38]. In the present study, the tissue culture plate method was used to test the ability of QAH, QAH-Pro, QAL and QAL-Pro to prevent biofilm formation by P. aeruginosa and S. epidermidis.…”
Section: Prevention Of Biofilm Formationmentioning
confidence: 99%
“…Thus, testing the antimicrobial properties of new compounds not only against exponentially growing bacterial cells but also against biofilms is mandatory. Ability of quaternized Ch-derivatives to interfere with biofilm formation is a promising but still relatively poorly investigated subject [37,38]. In the present study, the tissue culture plate method was used to test the ability of QAH, QAH-Pro, QAL and QAL-Pro to prevent biofilm formation by P. aeruginosa and S. epidermidis.…”
Section: Prevention Of Biofilm Formationmentioning
confidence: 99%
“…Chitosan can also play a role of the effective polymer matrix for the different mineral phosphate fillers; this is important in the view of a design of bone implants [2][3][4]. The presence of a positive charge on the ammonium groups of the polymeric chains imparts to chitosan the ability to connect with the cellular walls of the pathogenic bacteria [11,12], resulting in a death of them, and with the mucous membranes [13,14]. In addition, chitosan possesses good adhesion to the stromal cells; this is important for the design of the scaffolds [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium alloys, mainly Ti-6Al-4V, are commonly used in orthopedic surgery and traumatology due to their well-known physico-chemical properties and biocompatibility (16)(17)(18). To date, most of the methods used to manufacture nanotubular oxide layers with potential biomedical applications have been implemented in pure titanium (19)(20)(21)(22)(23)(24)(25)(26). Recently, we demonstrated that fluorine (F) doping during the anodizing process of Ti-6Al-4V decreases staphylococcal adherence by about 50% (27) and that F doping, together with the nanostructure resulting from the anodizing process, improves the osseointegrative properties by favoring matrix mineralization of osteoblastic cells (28).…”
mentioning
confidence: 99%